Teknis Komunikasi Dalam Peluang Usaha Photography Di Prince Studio Photography Padang - Shadikyanto, Fadjri; ., Defhany (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This final assignment of scientific paper writing is conducted to understand the communication efforts that can be observed in a professional interaction. In this case, the author focuses observations with the title "Observation of Technical Communication in Photography Business Opportunities at Prince studio photography Padang". It is a final study of scientific work aimed at exploring and analyzing the communication interactions that occur within the photography business environment, specifically at Prince studio photography Padang. In this context, the AIDDA theory (Attention, Interest, Desire, Decision, Action) is used as a framework to understand the communication process that occurs between the photography studio and its potential customers. This scientific paper uses a structured participant observation method to collect data. The results of the scientific paper show that in efforts to build relationships with customers, the photography studio uses the AIDDA theory as a communication technique, starting from attracting attention, generating interest, creating desire, encouraging decision-making, to prompting purchase actions. Additionally, it was also found that aspects such as visual impression, personal interaction, and marketing strategies play a significant role in influencing the effectiveness of communication in the context of photography business.